EVALUASI KEBIJAKAN PELAKSANAAN LATIHAN OPERASI MILITER TNI AL DALAM RANGKA MEMPERTAHANKAN STABILITAS EKOSISTEM - Anwar Kurniadi (Program Studi Manajemen Lingkungan, 2014)
This research aimed to evaluate the policy implementation of Armada Jaya Military Operation Exercise of Indonesia Navy in Sangatta 2012, East Kutai District, East Kalimantan. In frame of sustain ecosystem stability. The method of this research was policy research with content analysis design. The results of this research was expect to be recommendation to the Minister of Defence and Commander in Chief and Chief of Staf Indonesia Naval in order to make new regulation act of Military Operation Exercise in Indonesia that sustainable environment. The data were collected through observation, interviews, taking specimens, recording and documentation.The result showed that 1) the location of military operation is able to be exercise area and the conducting of Armada Jaya Military Operation Exercise were not follow yet the rule of Protection; 2) no impact to the environment, eventhough could not conduct Amdal, audit and restoration of environment, and involved less institusional and also social communities.The recommendation were to Defence Ministery and Commander in Chief of TNI to make new rule and also the new body of environment, while Chief of Staf Indonesia Navy have to make new rule of environment that account more technical operation, and make new Body of Environment and also conduct cooperation with Minister of Environment and Royal Australian Navy to educate and training Officers about environment in war military operation or other than war.